National and regional registries for congenital heart diseases: Strengths, weaknesses and opportunities. (1st September 2021) - Chami, Jason; Nicholson, Calum; Strange, Geoff; Cordina, Rachael; Celermajer, David S.
Abstract: Background: We aim to establish a new and informative bi-national Registry for Congenital Heart Disease (CHD) patients in Australia and New Zealand, to document the burden of disease and clinical outcomes for patients with CHDs across the lifespan. When planning for the implementation of this Registry, we sought to evaluate the strengths and weaknesses of existing national and large regional CHD databases. Methods: We characterised 15 large multi-institutional databases of pediatric and/or adult patients with CHD, documenting the richness of their datasets, the ease of linkage to other databases, the coverage of the target cohort and the strategies utilised for quality control. Results: The best databases contained demographic, clinical, physical, laboratory and patient-reported data, and were linked at least to the national/regional death registry. They also employed automatic data verification and regular manual audits. Coverage ranged from around 25% of all eligible CHD cases for larger databases to near 100% for some smaller registries of patients with specific CHD lesions, such as the Australia and New Zealand Fontan Registry. Conclusions: Existing national and regional CHD databases have strengths and weaknesses; few combine complete coverage with high quality and regularly audited data, across the broad range of CHDs. Highlights: We found 15 national/regional registries of congenital heart disease worldwide. Registry coverage ranged from 25 to 100% of all eligible cases. The best registries contain demographic, clinical, physical, and laboratory data. Regular verification is essential for quality data and valid statistical findings.